2013
DOI: 10.1653/024.096.0227
|View full text |Cite
|
Sign up to set email alerts
|

Age Preference and Fitness ofMicroplitis manilae(Hymenoptera: Braconidae) Reared onSpodoptera exigua(Lepidoptera: Noctuidae)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Most of the studies revealed that host age is an important factor that is considered by the parasitoids (Jowyk & Smilowitz 1978;Vinson & Iwantsch 1980) because the parasitoids must be provided with a suitable environment (the hosts and their feeding habitat) for their offspring (Qiu et al 2013;Chu et al 2014). Unlike gregarious koinobiont parasitoids, which prefer later instars in order to produce more offspring (Elzinga et al 2003), solitary parasitoids choose slowly-growing larvae as their hosts (Mironidis & Savopoulou-Soultani 2009;van Nouhuys et al 2012) and they regulate and adjust host development rate in favor of their own development (Khafagi & Hegazi 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies revealed that host age is an important factor that is considered by the parasitoids (Jowyk & Smilowitz 1978;Vinson & Iwantsch 1980) because the parasitoids must be provided with a suitable environment (the hosts and their feeding habitat) for their offspring (Qiu et al 2013;Chu et al 2014). Unlike gregarious koinobiont parasitoids, which prefer later instars in order to produce more offspring (Elzinga et al 2003), solitary parasitoids choose slowly-growing larvae as their hosts (Mironidis & Savopoulou-Soultani 2009;van Nouhuys et al 2012) and they regulate and adjust host development rate in favor of their own development (Khafagi & Hegazi 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A batch of 10 host larvae was dissected on each consecutive day to assess the development of the eggs. Each immature stage was recorded as egg, larva, or pupa (Qiu et al 2013). …”
Section: Development Of Immature Stages Of M Similismentioning
confidence: 99%
“…The intrinsic rate of increase can be also used to determine the finite rate of increase (λ), which depicts the number of times the population increases per unit time in a generation. Population growth parameters such as intrinsic rate of increase, net reproductive rate, and finite rate of increase are influenced by nature and quality of the host (Qiu et al 2013).…”
Section: Population Growth Parametersmentioning
confidence: 99%
“…Our results support previous observations reporting a higher suitability of two and three-day-old M. vitrata caterpillar to Apanteles taragamae (Viereck) (Hymenoptera: Braconidae) 24 . In the same vein, the second instar of Spodoptera exigua (Hübner) (Lepidoptera: Noctuidae) was identified as the most suitable host stage for Microplitis similis (Lyle) (Hymenoptera: Braconidae), based on the high values of r and Ro 29 . It was shown that parasitizing early host stages can reduce the development time in koinobionts parasitoids 16 ; however, adult fitness of the offspring may be affected, in terms of short life expectancy, small size eggs, and reduced oviposition period 30 .…”
Section: Discussionmentioning
confidence: 99%